Aquirufa ecclesiirivi sp. nov. and Aquirufa beregesia sp. nov., isolated from a small creek and classification of Allopseudarcicella aquatilis as a later heterotypic synonym of Aquirufa nivalisilvae. Issue 8 (13th August 2020) - Pitt, Alexandra; Koll, Ulrike; Schmidt, Johanna; Hahn, Martin W.
Abstract : Two bacterial strains, 50A-KIRBA T and 50C-KIRBA T, were isolated from the same freshwater creek located near Salzburg, Austria. They showed 16S rRNA gene sequence similarities to Aquirufa nivalisilvae of 100 and 99.9 %, respectively. A genome-based phylogenetic reconstruction with amino acid sequences of 119 single-copy genes suggested that the new strains represent two new species of the genus Aquirufa . Pairwise calculated whole-genome average nucleotide identity (gANI) values ranging from 85.4 to 87.5 % confirmed this conclusion. Phenotypic, chemotaxonomic and genomic traits were investigated. Like strains of other Aquirufa species, 50A-KIRBA T and 50C-KIRBA T grew aerobically and chemoorganotrophically, were rod-shaped, red-pigmented and motile, most likely by gliding. They could be distinguished by slight differences in the chemotaxonomic features. We propose to establish for strain 50A-KIRBA T (=CIP 111735 T =LMG 31080 T ) as type strain the name Aquirufa ecclesiirivi and for strain 50C-KIRBA T (=CIP 111736 T =LMG 31501 T ) as type strain the name Aquirufa beregesia . Furthermore, the relationship between the type strains of Aquirufa nivalisilvae (59G-WUEMPEL T ) and Allopseudarcicella aquatilis (HME7025 T ) was investigated. Results of polyphasic analyses, especially a gANI value of 97.6 %, as well as the genome-based phylogenetic reconstruction, suggested that Allopseudarcicella aquatilis is a heterotypic synonym of Aquirufa nivalisilvae . According to rule 24b of the International Code of Nomenclature of Prokaryotes we propose to classify strain HME7025 as Aquirufa nivalisilvae and provide an emended description for the latter.